Pre-operative counselling for laryngectomy patients: a systematic review. Issue 1 (16th November 2015) - Fitzgerald, E; Perry, A
Abstract: Objectives: This study aimed to undertake a systematic review of the literature about pre-operative counselling for laryngectomy patients, identify its practice and patient and (where possible) carer perceptions. Methods: A search strategy was formulated using a concept map and a Population, Intervention, Comparative Interaction and Outcomes ('PICO') schema. All publications from 1975 to 2015 reporting pre-operative counselling of laryngectomy patients were included. Papers were retrieved and critiqued, and those included were assigned a level of evidence (according to the Joanna Briggs Institute schema). Results: Of the 56 papers retrieved, 21 were included in the review. The literature is limited: studies demonstrate bias and are of poor methodological quality. There are clear, persistent reports by patients and carers of shortfalls in clinical practice. Conclusion: Studies on pre-operative counselling for laryngectomees are flawed in design and represent weak levels of evidence. Pre-operative counselling has not been operationalised, resulting in differing paradigms being examined. Aggregation of data and/or results is not possible and the veracity of many studies is questioned.